Tracing the spectral bodies and ghostly landscapes in Iraqi fiction - Ashraf, Yousra; Nusrat, Aasia; Khan, Sardaraz (Penerbit Universiti Kebangsaan Malaysia, 2025)
This research examines the ghostly materiality and phantasmal legacy that haunt the collective psyche of the Iraqi people, as documented through the devastation and subliminal changes in the war-torn landscape, as reflected in the chosen works of fiction. The study investigated the transformation of these places ravaged by war into ghostly records that disrupt the temporal and spatial bounds. This paper presents an investigation into the two texts, Frankenstein in Baghdad by Ahmed Saadawi and The Corpse Exhibition by Hassan Blasim, through the lens of Jo Frances Maddern and Peter Adey’s technique of mapping ‘Spectro-geographies,’ employing a content-based textual analysis of the chosen texts. The research particularly looked at the suffering of Iraqis within these texts and how they made sense of the constant inconsistency that emerged from the ruination and turmoil that had visited the Iraqi land, the gothic nature of the war, and its several aftermaths. Through the notion of spectro-geography, the research stressed the landscape’s struggle to come to terms with its forever changed and constantly altering phantasmic character and primal reality.